Energy project management system: benefits, principles and risks - Dedelyuk, Kateryna Yurivna (НТУ "ХПІ", 2016)
The essence of an effective energy project management system was described, as well as the main benefits of its implementation at the company level were characterized. Such outcomes as possible savings unlocking, improving risk management, reliability and productivity, reputational issues where described as key results from realization of an energy project management system. Among the main principles according to which an effective energy project management should be implemented the fallowing aspects were discussed: leadership and responsibility, energy policy and energy performance, communication and continuity of energy policy. The conclusions about the main risks that may occur during implementation of an effective energy project management system were also systematized in this article.

У статі представлено сутність ефективної системи управління енергетичними проектами, окреслено основні ризики та переваги для компанії в ході реалізації менеджменту. Серед основних принципів, яких слід дотримуватися при ефективному управлінні енергетичними проектами виділено такі: лідерство і відповідальність, енергоефективність, взаємозв‘язок елементів енергетичної політики. Висновки про основні ризики, які можуть виникнути в ході реалізації ефективної системи енергетичного проектного менеджменту також були систематизовані в цій статті.
Система управління енергетичними проектами: переваги, принципи і ризики
Keywords: energy project; management system; benefits; improvement; principle; energy efficiency; проект енергетичний; поліпшення; енергоефективність